Spherical standing burning wave with external automatic reactivity control - Leleko, Yu.Y.; Gann, V.V.; Gann, A.V. (Вопросы атомной науки и техники, 2019)
Neutron kinetics of a nuclear burning wave in moving incompressible neutron-multiplying medium in the presence of nuclear reactions is developed. A spherical reactor is considered, where fuel moves with acceleration to the center of the reactor at a velocity V(r)=VR(R/r)², and the burning wave travels radially from the center to periphery. The fuel that came to the origin was unloaded from the reactor, and U-238 was loaded to the peripheral area at the same rate. Comparison of theoretical results with computer simulation using MCNPX code was performed. Була розвинена нейтронна кінетика стоячої хвилі ядерного горіння в нейтронно-розмножуючім середовищі, котре не стискається та є рухомим, при наявності ядерних реакцій. Розглянуто сферичний реактор, в якому хвиля ядерного горіння рухається радіально від центра, а паливо – до центра реактора. Показано, що при підживленні такої системи ²³⁸U в ній може існувати сферична стояча хвиля ядерного горіння. Проведено порівняння теоретичних результатів з даними чисельного моделювання такого реактора з використанням коду MCNPX. Была развита нейтронная кинетика стоячей волны ядерного горения в нейтронно-размножающей среде, которая не сжимается и является подвижной, при наличии ядерных реакций. Рассмотрен сферический реактор, в котором волна ядерного горения движется радиально от центра, а топливо – в центр реактора. Показано, что при подпитке такой системы ²³⁸U в ней может существовать сферическая стоячая волна ядерного горения. Проведено сравнение теоретических результатов с данными численного моделирования такого реактора с использованием кода MCNPX.